Music and memory - Jaehnichen, Gisa (Universiti Putra Malaysia Press, 2012)
Music and memory are linked to each other in different ways and with different meanings. The physiological aspect of memory in its musical dimension, which has been discussed mostly outside of musicology, is only one part of it. Previous psychological research on musicality and its role for human development could raise public attention, and has led us to new insights as well as to cultural misinterpretations. These rather popular aspects have to be taken up and re-examined from the perspective of modern musicology, dance and theatre studies, of which include interdisciplinary approaches and detailed nalytical studies in a wider context of the performing arts and their steadily changing sound environment.This fourth volume of the UPM book series on music research is dedicated to the topic “Music and Memory”. A wide range of different studies provided by fifteen authors are arranged in the order of themes on fieldwork related issues, ethnomusicological analysis, physiological issues under different historical and educational viewpoints, composition techniques and audio technology.